Emergence and Phylogenetic Analysis of a Getah Virus Isolated in Southern China - Ren, Tongwei; Mo, Qingrong; Wang, Yuxu; Wang, Hao; Nong, Zuorong; Wang, Jinglong; Niu, Chenxia; Liu, Chang; Chen, Ying; Ouyang, Kang; Huang, Weijian; Wei, Zuzhang (Frontiers in Veterinary Science, 2020)
Getah virus (GETV) has caused many outbreaks in animals in recent years. Monitoring of the virus and its related diseases is crucial to control the transmission of the virus. In the summer of 2018, we conducted routine tests on clinical samples from different pig farms in Guangxi province, South China, and isolated and characterized a GETV strain, named GX201808. Cytopathic effects were observed in BHK-21 cells inoculated with GX201808. The expression of E2 protein of GETV could be detected in virus-infected cells by indirect immunofluorescence assays. Electron microscopic analysis showed that the virus particles were spherical and 70 nm in diameter with featured surface fibers. The multistep growth curves showed the virus propagated well in the BHK-21 cells. Molecular genetic analysis revealed that GX201808 belongs to Group 3, represented by Kochi-01-2005 isolated in Japan in 2005, and it clustered closely with the recently reported Chinese strains isolated from pigs, cattle, and foxes. A comparison of the identities of nucleotides and amino acids in the coding regions demonstrated that the GX201808 showed the highest amino acid identity (99.6%) with the HuN1 strain, a highly pathogenic isolate resulting in an outbreak of GETV infection in swine herds in Hunan province in 2017. In the present study, GETV was identified and isolated for the first time in Guangxi province of southern China, suggesting that future surveillance of this virus should be strengthened.